Simple implementation of plain woven polypropylene fabric. (February 2018) - Venter, Martin P; Venter, Gerhard
With increased utilisation of simple fabrics in technical engineering and manufacturing environments the need for suitable, easy to implement material representations in simulation software has increased. A simple implementation of plain woven polypropylene fabric for inflation simulation of dunnage bags is developed. Only standard finite element software packages and a simple material calibration protocol based on numerical optimisation were used to generate a homogenised material representation for the in-plane properties of plain woven polypropylene undergoing both loading and unloading. This is achieved by performing a simple material test that represents the in situ loading state of the material, measuring the applied load and material deformation in response to that load, and mapping that response to a simulation of the same test by means of an inverse problem statement. Following the proposed method, a material response model for plain wove polypropylene was developed that captures the major responses of a measured woven test specimen.